Pengaruh variasi suhu annealing terhadap struktur dan ukuran butir silika dari abu tongkol jagung menggunakan X-Ray Diffractometer (The effect of annealing temperature variations on the structure and grain size of silica from corn cobs ash using X-Ray Diffractometer) - Yoza Monalisa; Djusmaini Djamas; - Ratnawulan (Department of Physics – Universitas Negeri Padang UNP, 2013)
ABSTRACTThe development of technology and the use of silica in the industry is increasing, especially in the use of silica in the small particle size to the scale of microns or even nanosilika. The increasing need for silica it is necessary to find alternative materials that can be updated to produce silica. One is corn that has not been optimized. This research aims to investigate the structure and grain size of corn cob ash. This research is a form of experimentation with free variable 10000C annealing temperature and 11000C with a time of 6 hours of detention, control variables such as the mass of corn cobs, chemicals, and filter paper used. The dependent variable measures the levels of silica and silica crystals. Ash obtained was analyzed by gravimetric methods. Later in the annealing temperature of 10000C and 11000C for 1 hour will be obtained silica powder. Silica powder obtained by XRD to determine the crystal structure and the determination of the crystal grain size using Equation Schherer. After data collection and analysis of data obtained from crystalline silica structure is a diamond cubic structure with lattice parameter (a) is 7.01 Å. Grain size of the smallest crystals obtained at 11000C annealing temperature is 11.38 nm and the size of the crystal grain size of the greatest at 10000C annealing temperature is 40.83 nm. Keywords: grain structure, grain size, diffraction